Apoptosis Exerts a Vital Role in the Treatment of Colitis-Associated Cancer by Herbal Medicine - Ruimin Tian; Ruimin Tian; Xianfeng Liu; Yanqin Luo; Shengnan Jiang; Hong Liu; Fengming You; Chuan Zheng; Jiasi Wu (Frontiers Media S.A., 2020)
Colitis-associated cancer (CAC) is known as inflammatory bowel disease (IBD)-developed colorectal cancer, the pathogenesis of which involves the occurrence of apoptosis. Western drugs clinically applied to CAC are often single-targeted and exert many adverse reactions after long-term administration, so it is urgent to develop new drugs for the treatment of CAC. Herbal medicines commonly have multiple components with multiple targets, and most of them are low-toxicity. Some herbal medicines have been reported to ameliorate CAC through inducing apoptosis, but there is still a lack of systematic review. In this work, we reviewed articles published in Sci Finder, Web of Science, PubMed, Google Scholar, CNKI, and other databases in recent years by setting the keywords as apoptosis in combination with colitis-associated cancer. We summarized the herbal medicine extracts or their compounds that can prevent CAC by modulating apoptosis and analyzed the mechanism of action. The results show the following. (1) Herbal medicines regulate both the mitochondrial apoptosis pathway and death receptor apoptosis pathway. (2) Herbal medicines modulate the above two apoptotic pathways by affecting signal transductions of IL-6/STAT3, MAPK/NF-κ B, Oxidative stress, Non-canonical TGF-β1, WNT/β-catenin, and Cell cycle, thereby ameliorating CAC. We conclude that following. (1) Studies on the role of herbal medicine in regulating apoptosis through the Ras/Raf/ERK, WNT/β-catenin, and Cell cycle pathways have not yet been carried out in sufficient depth. (2) The active constituents of reported anti-CAC herbal medicine mainly include polyphenols, terpenoids, and saccharide. Also, we identified other herbal medicines with the constituents mentioned above as their main components, aiming to provide a reference for the clinical use of herbal medicine in the treatment of CAC. (3) New dosage forms can be utilized to elevate the targeting and reduce the toxicity of herbal medicine.